Food supplement consumption and its perceived benefits among IIUM students: A comparison study between health-related and non-health related undergraduate students - Sidek, Suriati; S. Mahdzir, Sharifah Farhana (Nutrition Society of Malaysia, 2017)
It was suggested that the misperceptions towards the food supplement consumption and its perceived benefit among university students may lead to the misuse of it. Therefore, the present study aimed to compare the food supplement consumption and its perceived benefits among health-related and non-health-related undergraduate students of International Islamic University Malaysia (IIUM). A total of 178 participants comprising of 98 health-related and 80 non-health-related undergraduate students were participated in this cross-sectional study. The items in the questionnaire were adapted from the Malaysian Adult Nutrition Survey (MANS 2014). The food supplements assessed include non-vitamin and non-minerals (NVNM) and vitamins and minerals (VM). The results showed that non-health-related students were more likely to consume NVNM (46.3%) than health-related students (37.8%). For the consumption of VM, both health-related and non-health-related students reported a similar pattern of consumption which are 43.9% and 42.5%, respectively. The most frequently consumed NVNM supplement were fish oil and collagen whereas, vitamin C is the most VM supplement taken by participants. The main reason for taking NVNM and VM supplements was for health purposes and most of the participants claimed that they feel healthier after consuming food supplement. These findings revealed that food supplement consumption was prevalent among university students, regardless of their field of study because of its perceived benefits.